Peranan Market Orientation, Inovasi Produk dan Competitive Advantage Terhadap Kinerja Pemasaran Usaha Songket di Kota Sawahlunto - Ash Shadiq Egim; Hardi Citra Sukma Putri (Universitas Negeri Padang, 2022)
This study was conducted to determine the effect of market orientation, innovation, and competitive advantage on marketing performance at CV Songket Aina in Sawahlunto City. The analytical technique used in this research is quantitative with multiple linear regression analysis. This study used 97 respondents as research samples by conducting a survey to Aina songket consumers in Sawahlunto with incidental sampling technique. The results of the study prove that the three marketing performance variables, which consist of market orientation, product innovation, and competitive advantage, have a positive and significant effect on purchasing decisions at Songket Aina Silungkang. Of the three variables, all variables have a significant effect. The ability of the independent variable to the dependent variable is 92.4%.Keyword:Market Orientation, Innovation, Competitive Adventage, Marketing Performance.